Influence of Magnetized Mixing Water on Different Levels of Concrete Strength using Different Curing Processes - Hussein, Dhuha M.; Abbas, Zena K. (Engineering, Technology & Applied Science Research, 2024)
This study investigated the impact of using Magnetic Water (MW) in concrete mixes on the mechanical properties of three normal concrete strength grades (15 MPa, 27.5 MPa, and 40 MPa) cured with three different methods (normal curing, water spraying, and coating). Compressive, flexural, and splitting strengths were tested. Results revealed that for the 15 MPa concrete, water spraying reduced compressive strength by 15.76% at 28 days compared to normal curing while coating curing increased it by 15.63%. Similar trends were observed for the 27.5 MPa (13.98% decrease for spraying, 13.60% increase for coating) and 40 MPa (10.81% decrease for spraying, 10.60% increase for coating) concrete grades. Flexural and splitting strength tests followed a similar pattern. For all concrete grades, water spraying led to reduced strength, while coating curing improved it. Overall, coating curing yielded the most favorable results across all strength grades, with the 15 MPa concrete showing the most significant improvements. These findings highlight the potential benefits of utilizing magnetic water in combination with coating curing to enhance the mechanical properties of concrete.